Trends and Challenges in Sustainable Broiler Farming in Sudan - Modawy Abdelgader Elbasheer Altayb; Fani Dwi Evadewi (Faculty of Animal Husbandry, Wijayakusuma Purwokerto University, 2025)
This study on sustainable broiler farming in Sudan uses a mixed-methods approach, combining primary data from 250 farms (multistage stratified sampling) with 10 years of secondary data to analyze trends and challenges. Quantitative analysis shows the sector is dominated by small-scale farms (65%). The average flock size is 1,200 birds with a 35-day cycle, and feed accounts for 60% of costs. Temporal analysis reveals 3.2% annual production growth (reaching 150 million birds in 2023), but high market price volatility (SD 12%) and an average mortality rate of 8.5%, driven by diseases like Newcastle and avian influenza. Mortality is strongly correlated with poor biosecurity (r = 0.68). Regression models confirm that biosecurity, feed quality, and water management significantly impact mortality. Only 40% of farms meet the sustainability threshold. Qualitative interviews highlight persistent challenges: limited access to quality feed (protein), water scarcity, poor cold chain logistics, and policy gaps. Modeling confirms a 20% biosecurity improvement could reduce mortality by 2%. The study concludes that despite sector growth, significant structural challenges in resource management (feed, water), disease control, and policy must be addressed to achieve sustainability.